2009
DOI: 10.1117/12.805977
|View full text |Cite
|
Sign up to set email alerts
|

Measuring visual discomfort associated with 3D displays

Abstract: Some people report visual discomfort when watching 3D displays. For both the objective measurement of visual fatigue and the subjective measurement of visual discomfort, we would like to arrive at general indicators that are easy to apply in perception experiments. Previous research yielded contradictory results concerning such indicators. We hypothesize two potential causes for this: 1) not all clinical tests are equally appropriate to evaluate the effect of stereoscopic viewing on visual fatigue, and 2) ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Pala et al 6 found that perceived workload was increased in the presence of crosstalk. In addition, several studies have reported that viewing comfort was reduced as crosstalk was increased [7][8][9] particularly for images containing large disparities 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Pala et al 6 found that perceived workload was increased in the presence of crosstalk. In addition, several studies have reported that viewing comfort was reduced as crosstalk was increased [7][8][9] particularly for images containing large disparities 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Pala et al [12] found that perceived workload increased in the presence of crosstalk in a task where observers were asked to align rods in depth. Still other studies have reported reduced visual comfort with increasing crosstalk [2], [13], [14]. Furthermore, crosstalk over 5% was found to cause a reduction in viewing comfort, especially for images containing large disparities [2].…”
mentioning
confidence: 80%
“…Therefore, it is possible that the evaluation of fatigue using only one indicator leads to low reliability. The evaluation of fatigue using multiple indicators is desirable and may increase the reliability of evaluation [16]. However, researches about the integration of multiple objective indicators, their variations along time and sensitivities to reflect subjective visual fatigue are rare.…”
Section: Introductionmentioning
confidence: 98%